Does COVID-19 Affect The Share Market Volatility In Indonesia? - Purwanto Widodo; Faizi (Jurnal Manajemen, 2023)
Volatility in financial markets reflects the level of risk that will be faced by investors due to fluctuations in stock price movements and stock returns which indicate the uncertainty of returns that investors will receive. This study uses daily data on JCI returns for the period January 1 2017 to October 30 2021 with the aim of modeling the volatility of JCI returns both before the Covid-19 crisis and during Covid-19. In addition, it is intended to see changes in the volatility of JCI returns due to the Covid-19 crisis. The research findings are that both before the crisis and during Covid-19 the appropriate volatility model is a model that has a leverage effect problem, namely EGARCH (1,1). there is a difference in the stock price index EGARCH return model between before and during Covid-19. Another finding is the influence of the variance in the previous period, the previous model was higher than during Covid-19.